P‐122: Polymer‐Stabilized Blue‐Phase Liquid Crystal Displays using interdigitated Corrugated Electrodes. Issue 1 (May 2016) - Wei, Shih-Hsien; Chang, Chia-Liang; Chang, Yu-Chuan; Choi, Wing-Kit
Abstract : We propose an interdigitated electrode design to improve the transmission of a Polymer Stabilized Blue Phase Liquid Crystal (PS‐BPLC) display based on a corrugated electrode. By using our modified new design, it is possible to further improve the transmission of this BPLC display by 5% due to the reduction of "dead zones" caused by the disclination lines, while keeping a low operation voltage below 10V. PS‐BPLC display based on corrugated electrode is attractive since it can offer both low operation voltage and high transmission at the same time.